2002
DOI: 10.1007/s00167-002-0301-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of meniscus repair with a bioabsorbable arrow: a 2- to 3-year follow-up study

Abstract: In a clinical study with the bioabsorbable Bionx Meniscus Arrow we prospectively evaluated 113 consecutive patients (113 menisci) after all-inside meniscus repair. Repairs were performed in either the medial (80.5%) or lateral (19.5%) posterior horn in the red-red or red-white meniscal zone; 66% of patients underwent concomitant ACL reconstruction. Assessment was based on history, clinical examination, and Lysholm [37] and Cincinnati Knee Scores. After a mean follow-up was 33 months (range 24-43; n=105) 21 (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 45 publications
2
52
1
6
Order By: Relevance
“…2,10,17 The biomechanical characteristics of the new flexible meniscus suture anchors evaluated in this study were either comparable (RapidLoc) or superior (FastT-Fix) to the biomechanical characteristics of the 10-mm Meniscus Arrow. Therefore, the clinical use of the RapidLoc and the FastTFix can be justified from the biomechanical point of view.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…2,10,17 The biomechanical characteristics of the new flexible meniscus suture anchors evaluated in this study were either comparable (RapidLoc) or superior (FastT-Fix) to the biomechanical characteristics of the 10-mm Meniscus Arrow. Therefore, the clinical use of the RapidLoc and the FastTFix can be justified from the biomechanical point of view.…”
Section: Discussionmentioning
confidence: 84%
“…Other authors, using new rigid anchor techniques with lower biomechanical fixation strengths, have suggested a more careful rehabilitation approach. 2,17 Kohn and Siebert 26 demonstrated that vertical suture techniques are superior to horizontal suture techniques. This finding could be confirmed in many other investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic outside-in and inside-out techniques, despite their widespread acceptation and the excellent reported _results, have been associated with a relatively high risk of neurovascular injuries or deep infections [12]. However, the all-inside technique for meniscus repair has gained popularity recently, as it is a safe and fast fixation technique [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, preservation of meniscal tissue is an over whelming rationale in young active patients and several authors have demonstrated that tears located in the central onethird avascular zone can be successfully repaired. 6,12,58,59,68,80,82,90 sults of meniscal repair using fixators, such as arrows, 22,29,43,48,50,83,84 staples, 49 and all-inside biodegradable screws 32,38,69 ; however, arthroscopicassisted suture repair remains the gold standard and is our preferred method. In addition, we have demonstrated that a rehabilitation program that implements immediate knee motion the first postoperative day after meniscus repair (performed either alone or with anterior cruciate ligament [ACL] reconstruction) is not deleterious to the healing meniscus tissue and prevents knee arthrofibrosis.…”
mentioning
confidence: 99%